RESCUE OF COLLATERAL OBJECTS OWNED THIRD PARTIES DUE TO BREACH OF DEBTORS WITH SUBROGATION AS LEGAL REMEDIES IN SHIP CASES ABOVE 20 m3 - Syahril, Syahril; Hamler (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
Payments can also have limited consequences in the sense that these payments only result in the role of the Creditor being replaced by another Creditor and the Debtor will be faced with a new Creditor who has the right to request payment from the Debtor or what is known as Subrogation and in this study occurs in the case of ships over 20 m2 as a Hipotek . Ships can meet the criteria or requirements to become collateral for credit settlement in the form of a Hipotek. Ships As Collateral for Repayment of Credit where the Hipotek is a material right to immovable objects. Ships can be divided into two, namely those weighing above 20 m 3 and below 20 m 3 . This paper aims to find out which ships can be charged with a Hipotek, so that they can be used as collateral for credit repayment. The method used is normative legal research, namely an approach by studying the applicable laws and regulations. The conclusion of this paper is that a Hipotek is a form of credit repayment guarantee, which is regulated in Burgelik Wetboek . Hipotek can be applied to objects in the form of ships. Ships As Guarantees for Repayment of Credit where the Hipotek is a material right to immovable objects which in this study uses subrogation as a legal remedy used.